Current Progress in Nanotechnology Applications for Diagnosis and Treatment of Kidney Diseases. Issue 13 (29th June 2015) - Lee, Sue Hyun; Lee, Jung Bok; Bae, Min Soo; Balikov, Daniel A.; Hwang, Amy; Boire, Timothy C.; Kwon, Il Keun; Sung, Hak‐Joon; Yang, Jae Won
Abstract : Significant progress has been made in nanomedicine, primarily in the form of nanoparticles, for theranostic applications to various diseases. A variety of materials, both organic and inorganic, have been used to develop nanoparticles with promise to achieve improved efficacy in medical applications as well as reduced systemic side effects compared to current standard of care medical practices. In particular, this article highlights the recent development and application of nanoparticles for diagnosing and treating nephropathologies. Abstract : The complex landscape of renal anatomy that guides rational design of nanoparticles for renal applications is reviewed, and existing literature that employs various organic and inorganic nanoparticles to diagnose and/or treat renal diseases is further examined.